Pengujian Aplikasi Pemesanan Tiket Pesawat Berbasis Web dengan Menggunakan Metode Black Box dengan Teknik Equivalence Partitioning - Khantaqwa Amri; Mahdiyana Mahdiyana; Muhammad Yasir; Muhamad Zein Akbar; Aries Saifudin (CV. Multi Kreasi Media, 2022)
An error often occurs if you enter a name that does not match the e-ticket's KTP, but the e-ticket issued is the wrong e-ticket and does not match the original ID. When they were at the airport, before their flight, they were confused about what to do because if they didn't know for sure the respective airline's rules regarding these pseudonyms, they would be doing harm to the people involved. When testing the ticket booking application, testers use a testing technique that is a variation of the black-box technique: equipartition. This procedure is a test that relies on inputting information about each structure in the framework. In each menu, the information is tested and compiled to work either legally or illegally. If any errors are found, they will be fixed immediately. All information requirements have been checked, all requirements have been met and guaranteed to ensure a successful and error-free flight booking and all requirements have been properly met.